2011
DOI: 10.1159/000325058
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Rejection of the Young Child: Present Status of the Clinical Syndrome

Abstract: This article reviews severe disorders of the mother-infant relationship involving emotional rejection of the infant in the first year of its life. Infants exposed to their mother’s hatred and rage may suffer far-ranging and long-term disadvantages, and are at risk of maltreatment. Diagnosis, therapy and research have been hampered by the lack of recognition of this clinical syndrome in the classifications. The imminent revision of these classificatory systems must include them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 213 publications
(102 reference statements)
0
36
0
13
Order By: Relevance
“…The development of mother-infant emotional bonding is an extremely crucial process in the postpartum period (Brockington, 2011). Previous studies have found that some mothers do not immediately feel affection for their babies after their delivery; indeed, approximately 40% of primiparae feel indifferent about their newborn infants…”
Section: Introductionmentioning
confidence: 99%
“…The development of mother-infant emotional bonding is an extremely crucial process in the postpartum period (Brockington, 2011). Previous studies have found that some mothers do not immediately feel affection for their babies after their delivery; indeed, approximately 40% of primiparae feel indifferent about their newborn infants…”
Section: Introductionmentioning
confidence: 99%
“…This paper is an update of the article entitled ‘Maternal rejection of the young child: present status of the clinical syndrome', published by Psychopathology in 2011 [1]. The author searched for recent literature, mainly using Google Scholar (based on key publications), because PubMed is unhelpful in this area of psychiatry.…”
Section: The Scope Of This Reviewmentioning
confidence: 99%
“…Depression during pregnancy and after the birth is a strong association. As for the infant's behaviour, several papers [1] have established a link between infant illness or disability and child maltreatment, but again, assessment of the intermediary - aversion to the infant - has been omitted. Impaired bonding or pathological anger has been linked to colic [179,180] or sleep disturbance [181,182,183], and some of this evidence is recent.…”
Section: Causes and Consequencesmentioning
confidence: 99%
“…During this period, the parent-child relationship is crucial for the child's biological, cognitive, emotional, and social development (Belsky & Fearon, 2002;Feldman, 2007). One of the most important processes in the postpartum period is the postnatal bonding between the parents and the baby (Brockington, 2004(Brockington, , 2011).…”
Section: Introductionmentioning
confidence: 99%